Cervical Cancer Awareness and Screening in Botswana. Issue 4 (1st May 2012) - Mingo, Alicea M.; Panozzo, Catherine A.; DiAngi, Yumi Taylor; Smith, Jennifer S.; Steenhoff, Andrew P.; Ramogola-Masire, Doreen; Brewer, Noel T.
Abstract : Objective: Cervical cancer remains a leading cause of death in many developing countries because limited screening by Papanicolaou (Pap) smear. We sought to better understand women's beliefs about cervical cancer and screening in Botswana, a middle-income African country with high rates of cervical cancer. Methods: We interviewed 289 women attending general medicine or human immunodeficiency virus (HIV) clinics, where Pap testing was available, in Gaborone, Botswana, in January 2009. Results: About three fourths (72%) of the respondents reported having ever had a Pap smear; HIV-positive women were more likely to have had a Pap smear than HIV-negative women (80% vs 64%; odds ratio, 1.97; 95% confidence interval, 1.10–3.55). Screening was also more common among women who were older, had higher incomes, or had heard of cervical cancer. Almost all participants reported a desire to have a Pap smear. Reasons included to determine cervical health (56%), to improve overall health (33%), and to obtain early treatment (34%). About half (54%) of the respondents said they did not know what causes cervical cancer, and almost none attributed the disease to human papillomavirus infection. Conclusions: Study findings can inform interventions that seek to increase cervical cancer awareness and uptake of screening as it becomes more widely available.